TMS 2015 144th Annual Meeting &Amp; Exhibition 2015
DOI: 10.1007/978-3-319-48127-2_55
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Deformation Processing with Additive Manufacture of Ti-6Al-4V Components for Improved β Grain Structure and Texture

Abstract: With Ti alloys like Ti-6Al-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…[3] The benefits of this are much more isotropic and consistent mechanical properties. [2,29,30] Why interpass rolling is so effective in refining the grain structure, when applying relatively low applied plastic strains (< 20 pct), is still the subject of on-going research. However, Donoghue et al [31,32] suggested that deformation and rapid re-heating can cause twinning of the b grains when they re-grow, though this is understood to be normally less favorable in Ti64.…”
Section: Inter-pass Deformationmentioning
confidence: 99%
“…[3] The benefits of this are much more isotropic and consistent mechanical properties. [2,29,30] Why interpass rolling is so effective in refining the grain structure, when applying relatively low applied plastic strains (< 20 pct), is still the subject of on-going research. However, Donoghue et al [31,32] suggested that deformation and rapid re-heating can cause twinning of the b grains when they re-grow, though this is understood to be normally less favorable in Ti64.…”
Section: Inter-pass Deformationmentioning
confidence: 99%
“…Irrespective of the exact mechanism, the observation of the growth of new orientations on re-hearting, due to twinning of the phase caused by the application of a low applied strain in AM, could in principle contribute to explaining the origin of the refined equiaxed prior-grain structure and textural weakening seen when AM is combined with deformation techniques, as described in [7] and [8]. However, there are additional questions that have been raised by this study that will need further future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The high cost of this material, combined with the inherent difficulty of machining, makes the fabrication of Ti-6Al-4V aerospace components a natural match with the emerging technologies of Additive Manufacture (AM), that are capable of producing near-net-shape parts [2][3][4][5][6][7][8][9]. However, it is widely acknowledged that AM processes produce very different microstructures and textures to those that are traditionally developed through thermo-mechanical processing (TMP) [10], and this can lead to a different property balance in AM components that needs to be better understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations